2011
DOI: 10.1074/jbc.m110.167817
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs-10a and -10b Contribute to Retinoic Acid-induced Differentiation of Neuroblastoma Cells and Target the Alternative Splicing Regulatory Factor SFRS1 (SF2/ASF)

Abstract: MicroRNAs (miRNAs) are an emerging class of non-coding endogenous RNAs involved in multiple cellular processes, including cell differentiation. Treatment with retinoic acid (RA) results in neural differentiation of neuroblastoma cells. We wanted to elucidate whether miRNAs contribute to the gene expression changes induced by RA in neuroblastoma cells and whether miRNA regulation is involved in the transduction of the RA signal. We show here that RA treatment of SH-SY5Y neuroblastoma cells results in profound c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 80 publications
7
86
1
1
Order By: Relevance
“…This miRNA is a potent inducer of neuroblastoma and muscle cell differentiation (Huang et al 2010, Foley et al 2011, Meseguer et al 2011. As leptin is involved in neuronal network organization in the hypothalamus, we suggest that blocking leptin action early in life promotes neuronal differentiation instead of proliferation leading to the impairment of energy homeostasis later in life as our findings suggest.…”
Section: Figuresupporting
confidence: 63%
“…This miRNA is a potent inducer of neuroblastoma and muscle cell differentiation (Huang et al 2010, Foley et al 2011, Meseguer et al 2011. As leptin is involved in neuronal network organization in the hypothalamus, we suggest that blocking leptin action early in life promotes neuronal differentiation instead of proliferation leading to the impairment of energy homeostasis later in life as our findings suggest.…”
Section: Figuresupporting
confidence: 63%
“…A sharp change in Numb isoform expression was observed in P19 embryonal carcinoma cells when neuronal differentiation was stimulated by RA [201]. The molecular mechanism of Numb alternative splicing remains an open question, although RA-induced differentiation alters splicing machinery in P19 cells [202] and in SH-SY5Y neuroblastoma cells [203].…”
Section: Downstream Effectors Of Retinoic Acid Signaling Related To Nmentioning
confidence: 99%
“…Regarding the regulation of SRSF1 expression levels by miRNA, recent work from the Barettino laboratory (19) has shown that miR-10a and 10b directly target SRSF1 3 0 UTR, leading to SRSF1 mRNA destabilization during retinoic-acid induced differentiation of neuroblastoma cell line SH-SY5Y. In addition, changes in miR-10a and 10b levels alter SRSF1 regulatory activity both at alternative splicing and mRNA translation level, as evaluated by the analysis of tau exon 10 inclusion and translation of a reporter mRNA harboring an SRSF1-binding sequence, respectively.…”
Section: Post-transcriptional Regulation Of Sr Protein-coding Genesmentioning
confidence: 99%